European military rivalry, 1500-1750 - Hanlon, Gregory, 1953-
1 online resource
Keywords: “European Military Rivalry, 1500-1750: Fierce Pageant examines more than two hundred years of international rivalry across Western, Central, and Eastern Europe and the Mediterranean rim. Drawing heavily upon international scholarship over the last half-century, European Military Rivalry, 1500-1750: Fierce Pageant will be of great use to undergraduate students studying military history and early modern Europe“--